Old divergences in a boreal bird supports long-term survival through the Ice Ages - Saitoh, Takema (BioMed Central, 2010)
BACKGROUND: Unlike northern Europe and most of northern North America, the Eastern Palearctic and the northwesternmost tip of North America are believed to have been almost unglaciated during the Quarternary glacial periods. This could have facilitated long-term survival of many organisms in that area. To evaluate this, we studied the phylogeography in east Asia and Alaska of a boreal migratory passerine bird, the Arctic Warbler Phylloscopus borealis, and compared our results with published data on especially North American species. RESULTS: In a sample of 113 individuals from 18 populations we identified 42 haplotypes of the mitochondrial cytochrome b gene, which separated into three clades: A - Alaska and mainland Eurasia (except Kamchatka); B - Kamchatka, Sakhalin and Hokkaido; and C - Honshu, Shikoku and Kyushu (i.e. Japan except Hokkaido). The oldest split among these clades, between A/B and C, is estimated to have taken place sometime between the mid Pliocene and early Pleistocene, and the second divergence, between clades A and B, in the early to mid Pleistocene. Within all of the three main clades, there are signs of population expansion. CONCLUSIONS: The Arctic Warbler separated into three main clades in close succession around the Pliocene/Pleistocene border, with the two northern clades diverging last. All three clades probably experienced population bottlenecks during the Pleistocene as a result of range shifts and contractions, but nevertheless survived and maintained their integrities. Several other clades of Northeastern Palearctic birds are noted to have diversified during the Pliocene. In contrast, avian species or phylogroups presently occupying formerly glaciated North American ground are generally younger. The differences between these regions could be due to slower speciation rates in the Eastern Palearctic due to less fragmentation of forest habitats during glacial periods, or to longer survival of Eastern Palearctic clades as a result of less severe conditions in that region compared to northern North America. Several other Palearctic organisms show concordant biogeographical patterns to that of the Arctic Warbler, indicating common causes of their diversifications.